HUBUNGAN MOTIVASI BELAJAR DAN MANAJEMEN WAKTU DALAM MENINGKATKAN PRESTASI AKADEMIK PADA SISWA KELAS X SMA LAB SCHOOL SEMARANG - Setiarini, Avita nur (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2024)
The aim of this research is to identify the relationship between learning motivation and time management of class X students at SMA Lab School Semarang and academic achievement. This type of research is correlational research carried out in class X at SMA Lab School Semarang. The population in this study were all class X students, totaling 108. The sampling technique used Random Sampling technique consisting of 85 students. The instrument used uses a Likert scale, the analysis technique used is product moment correlation. Based on the results of the product moment correlation test, the learning motivation variable obtained r count < r table 0.854 > 0.210, the significance value was 0.000 < 0.05, the results of the time management correlation test obtained 0.789, while the academic achievement variable obtained a result of 0.671, which means that Ho is rejected and it can be concluded that the two variables are correlated. Then the correlation coefficient (r) is 0.854, 0.789, 0.671 with a positive level, so it can be concluded that there is a perfect positive relationship with a strong level of relationship.